Design and codification of the compound test in catching and delivering of the pivot player in holding the opponent, tackling towards, and going back of the defence player of the handball - Fathi, Moushriq Khaleel (International Journal of Psychosocial Rehabilitation, 2020)
The process of handing over or receiving the pivot player to and from the colleague that occurs during matches in defense situations aims to reduce his risk and get rid of the possibility of seizure and numerical superiority, then pounce on the opposing back-line player who poses a danger to the goal, as it needs concentration and harmony High between the two defenders, they come through continuous training, and they depend on the speed of performance and the correct timing between them to ensure the delivery and reception of the circuit player on the line of the goal area, so it was required that tests be available for sports skills in all games and handball and in particular defensive ones due to their scarcity, and the importance of this study comes from During the creation of a special modern test that measures this skill for the benefit of researchers, coaches and players alike, a small contribution from the researchers to serve the game of handball.